Electron donor and acceptor functionalized dithienylethenes: effects of charge density on photochromic properties. Issue 21 (16th May 2018) - Wan, Hao; Xue, Haodong; Ling, Yuan; Qiao, Yanjun; Chen, Yijing; Zhou, Gang
Abstract : The effect of charge density on the photochromic properties has been systematically investigated in donor/acceptor functionalized dithienylethenes. Abstract : Electron-donating triphenylamine and/or electron-withdrawing pyromellitic diimide (PMDI) are functionalized on dithienylethene (DTE) and three novel photochromic materials have been designed and successfully synthesized. All the compounds display reversible photochromism due to the molecular switching between ring-closed isomers upon UV light irradiation and ring-open isomers upon exposure to visible light. Thus they can be applied as an anti-counterfeiting ink. Moreover, the study of the photoswitching kinetics reveals that both the ring-closing and ring-opening reactions are first-order reactions. Further charge population analysis discovers that the electron densities of the substituents at the DTE core have a dramatic influence on the photochromic properties. The incorporation of electron-donating triphenylamine groups at the α-position of the thiophene rings in the DTE unit facilitates the ring-closing reaction upon UV light irradiation. In contrast, the substitution of an electron-withdrawing PMDI unit in the DTE unit is beneficial to the ring-opening reaction upon irradiation of visible light. This work may help to understand the photochromism of DTE derivatives and provide a pathway for designing DTE-based photochromes with more or less sensitivity to UV or visible light.